2023
DOI: 10.1101/2023.02.17.529028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide screen reveals Rab12 GTPase as a critical activator of pathogenic LRRK2 kinase

Abstract: Activating mutations in the Leucine Rich Repeat Kinase 2 (LRRK2) cause Parkinson’s disease. LRRK2 phosphorylates a subset of Rab GTPases, particularly Rab10 and Rab8A, and we showed previously that phosphoRabs play an important role in LRRK2 membrane recruitment and activation (Vides et al., 2022). To learn more about LRRK2 pathway regulation, we carried out an unbiased, CRISPR-based genome-wide screen to identify modifiers of cellular phosphoRab10 levels. A flow cytometry assay was developed to detect changes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 54 publications
(106 reference statements)
2
16
0
Order By: Relevance
“…2C. In agreement with previous studies, multiple Rab binding sites are detected in the Armadillo domain (Dhekne et al, 2023; Vides et al, 2022). However, district contact patterns with the enzymatic core (Roc-COR-Kinase) of LRRK2 have also been detected.…”
Section: Resultssupporting
confidence: 92%
“…2C. In agreement with previous studies, multiple Rab binding sites are detected in the Armadillo domain (Dhekne et al, 2023; Vides et al, 2022). However, district contact patterns with the enzymatic core (Roc-COR-Kinase) of LRRK2 have also been detected.…”
Section: Resultssupporting
confidence: 92%
“…In order define specific cellular machinery that is required for CASM-mediated LRRK2 activation, we performed a targeted siRNA screen focusing on the ATG8-related proteins that are lipidated as part of the CASM pathway. As expected, LRRK2 activity (measured by Rab10 phosphorylation) was reduced by the knockdown of LRRK2 and Rab10 itself as well as by knockdown of Rab12, a recently identified regulator of LRRK2 activity (Dhekne et al, 2023;Wang et al, 2023a)(Fig. 5A).…”
Section: Gabarap Is Required For Casm-dependent Lrrk2 Activationsupporting
confidence: 77%
“…Rab GTPases also act upstream of LRRK2 to promote its membrane recruitment and activation (Dhekne et al, 2023;Eguchi et al, 2018;Gomez et al, 2019;Lian et al, 2023;Pfeffer, 2022;Purlyte et al, 2018;Unapanta et al, 2023;Vides et al, 2022;Wang et al, 2023a). However, although Rab GTPases promote LRRK2 kinase activity in specific contexts, recent knockout mouse studies revealed the persistence of partial or even full LRRK2 kinase activity in multiple tissues even after depletion of key Rab proteins implicated in LRRK2 activation (Dhekne et al, 2023;Kalogeropulou et al, 2020). These results suggest the existence of additional factors that contribute to LRRK2 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, LRRK2 activation is clearly a complex process and could be achieved by other mechanisms, such as lipid oxidation, Rab12, and microtubule-based filamentation (11,12,(55)(56)(57)(58). This study focuses on Rab29-induced LRRK2 activation and provides a framework for interpreting disease mutations in the context of kinase activation.…”
Section: Discussionmentioning
confidence: 99%